To Share or Not to Share Knowledge: An Ethical Dilemma for UK Academics? - Patel, Mannisha; Ragsdell, Gillian (Journal of Knowledge Management Practice, 2011)
Effective knowledge sharing is at the heart of organisational life; for universities it is the core of their existence. Knowledge is shared not only with students and society, but it is also shared between Faculty staff and in collaborative arrangements with external enterprises. The need to disseminate knowledge so widely has drawn attention to related ethical considerations – this is the focus herein. This paper explores the ethical concerns raised about the sharing of knowledge by academics in two Faculties at a British university, and the influence of those concerns on the willingness of academics to share their knowledge. In doing so, the paper shares the findings of a pilot study and intends to prompt further debate about, and research into the relationship between ethics and knowledge sharing.